PENERAPAN ETIKA BISNIS ISLAM PADA PEMBUDIDAYA IKAN GUPPY (STUDI PADA GUPPYJUNIOR SURABAYA) - Maulana, Andriansyah Sulistyo; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
The high demand for ornamental fish like Guppy, both on local and international market, has increased the opportunity for Guppy fish cultivation. However, there are many people who lacks basic knowledge and technical support to cultivating Guppy. As a result, many fish that has been cultivated did not meet the standards on the market. The purpose of this research was to describe Islamic Business Ethics Application on Guppy's Farmers in Guppy Junior Surabaya. The researchers used descriptive-qualitative research methods to describe how was the cultivation process of Guppy fish by Guppy Junior Surabaya and to know whether the method is appropriate with Islamic Business Ethics. As for the method to collect data is using interviews, conducted on main and supporting sources, and followed by documentations and direct observation to obtain data. The results of this study state that in the process of guppy fish cultivation carried out by guppy junior surabaya, they are able to apply the principles of Islamic business ethics which include the principles of unity, balance, free will, responsibility, and honesty/kindness